Effects of 24-h acute total sleep deprivation on physiological coupling in healthy young adults - Liu, Hongyun; Yu, Xiaohua; Wang, Guojing; Han, Yi; Wang, Weidong (Frontiers in Neuroscience, 2022)
Sleep deprivation is associated with dysregulation of the autonomic nervous system, adverse cardiovascular events, cognitive and complex motor performance impairment. Less is known about the effects of acute total sleep deprivation (ATSD) on physiological coupling. We aimed to determine the effects of 24-hour ATSD on the physiological coupling between complex subsystems by evaluating the cardiorespiratory, cardiovascular and cortico-cardiac interactions. This study enrolled 38 young healthy participants aged 23.2±2.4 years. Multiple synchronous physiological signals including electrocardiography, photoplethysmography, bio-electrical impedance, electroencephalography, and continuous hemodynamic data, were performed over a baseline night after regular sleep and after a night with 24-hour ATSD in the supine position. The magnitude squared coherence, phase synchronization index and heartbeat evoked potential amplitudes, were obtained from 10-minute synchronous physiological recordings to estimate the coupling strength between two time series. Parameters of hemodynamic characteristics and heart rate variability were also calculated to quantify autonomic regulation. Results indicated that the magnitude squared coherence (0.38±0.17 vs. 0.29±0.12, p=0.015) between respiration and heart rate variability along with the magnitude squared coherence (0.36±0.18 vs. 0.27±0.13, p=0.012) between respiration and pulse transit time were significantly decreased after 24-hour ATSD. There were no significant differences (all p>0.05) in phase synchronization indices, heartbeat evoked potential amplitudes as well as other analyzed measurements between baseline and 24-hour ATSD states. We conclude that exposure to 24-hour ATSD appears to weaken the cardiorespiratory and respiratory-cardiovascular coupling strength of young healthy adults. These findings suggest that physiological coupling analysis may serve as a complementary approach for characterizing and understanding the complex effects of sleep deprivation.